Study on the Heterogeneity of Social Security Affecting the Sense of Security of Urban and Rural Residents. (9th May 2022) - Liu, Yuanfeng; Luo, Shujiao
Abstract : Social security is an important part of the national security system from the perspective of the overall security concept, and social security is an important influencing factor of social security. Using the CFPS2018 data, this study uses the critical weight method to measure residents' individual security and uses path analysis to empirically study the impact of endowment insurance and medical insurance on residents' security in urban and rural areas. The results show that the depth of endowment insurance has a significant positive impact on the sense of security of urban residents. The depth of meniscal insurance has no impact on the sense of security of urban residents. The depth of endowment insurance and medical insurance has a significant positive impact on the sense of security of rural residents. The depth of endowment insurance has a significant positive impact on the sense of security of urban residents. The influence of full sense is greater than that in rural areas, and the influence of meniscal insurance coverage depth on residents' sense of security in rural areas is greater than that in urban areas. Therefore, the impact of social security on residents' sense of security is heterogeneous between urban and rural areas. We should allocate the limited social security investment to urban and rural areas in a reasonable and balanced way to promote the overall sense of security of social residents. Integrate and improve the social security system and promote regional and group equity. Change the concept of government management, build a communication platform between the government and the people, and improve residents' subjective sense of security. We should continue to expand the coverage of the system, promote the coverage of basic social security projects, and improve the ability of urban and rural residents to cope with risks.